The heterogeneity of oxidized lipids in individual tumor cells reveals NK cell-mediated cytotoxicity by label-free mass cytometry. Issue 24 (22nd November 2022) - Shen, Zizheng; Yao, Huan; Yang, Jinlei; Pan, Xingyu; Zhao, Hansen; Han, Guojun; Zhang, Sichun; Zhang, Xinrong
Abstract : The heterogeneity of lipids and oxidized lipids such as PC(38:6) and PC(38:6-2OH) in individual tumor cells reveals NK cell-mediated cytotoxicity by label-free mass cytometry. Abstract : NK cell-mediated immunotherapy has received increasing attention in the past decade due to its efficacy and bio-safety. The composition and content of lipids in individual cells are closely related to NK cell-mediated cytotoxicity, especially polyunsaturated fatty acids (PUFA) which are oxidized during NK cell-mediated apoptosis. Here we investigated the changes of lipids in single HepG2 cells by label-free mass cytometry and obtained information on 53 lipids and 13 oxidized lipids after the interaction with NK92 MI cells. We found that the contents of lipids and oxidized lipids of HepG2 cells changed obviously during the NK cell-mediated apoptosis. The HepG2 cells could be classified into two phenotypes after co-culturing with NK92 MI cells based on the ratio of PC(38:6-2OH)/PC(38:6) in individual cells, which may serve as a feature to evaluate NK cell-mediated cytotoxicity. The present work used the lipids and oxidized lipids of individual cells to reveal the heterogeneity in NK cell-mediated apoptosis which would be a powerful method for evaluating the cytotoxicity of NK cells at the single-cell level.